Semantic Representation of Balinese Traditional Dance - Koten, Irianto Liko; Pramartha, Cokorda Rai Adi (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2020)
Bali is an island in Indonesia that is rich in culture, for example, is a traditional dance. The traditional dance performance is diverse from one village to another village in Bali. The traditional Balinese dance knowledge should be captured dan documented well in a digital form so that it can be shared easily to different people and generation across the world. The use of ontology as an information representation technique is the preferred solution in this matter because ontology can be used to enhance the development of semantic applications, especially when dealing with semantic webs. In this project, the ontology was built using Protege ontology development tool. We follow the methontology ontology development method where this methodology clearly describes each of its activity. In this study, we focus to describe two variants of Balinese traditional dance (Barong dance and Pendet dance). In the future, we expect that more type of dance can be documented using our proposed ontology. Keywords: Balinese Dance, Ontology,Semantic Web